On the Multiuser Diversity of Relay-Aided Downlink Systems Using Reduced Feedback - Yong-Up Jang; Won-Yong Shin (The Scientific World Journal)
We introduce an efficient multiuser scheduling method using amplify-and-forward relaying in relay-aided downlink systems, consisting of one base station (BS), one relay station, and multiple mobile stations (MSs). In our scheme, the BS opportunistically selects both the transmission mode, that is, either one- or two-hop transmission, and the desired user (i.e., the desired MS). Closed-form expressions for the average achievable rates are derived for the two transmission modes with multiuser scheduling, and its asymptotic solutions are also analyzed in the limit of large number of MSs. Based on the analysis, we propose a feedback-efficient two-step multiuser scheduling algorithm: the transmission mode selection followed by the user selection that only needs a partial feedback for instantaneous signal-to-noise ratios (SNRs) to the BS. We also analyze the average SNR condition such that the multiuser diversity gain is fully exploited for two-hop transmission. The proposed two-step scheduling algorithm exhibits the quite comparable achievable rates to those of the optimal one using full feedback information, while its required feedback information is reduced by half of the optimal one.